The effects of Using Games in Teaching and Learning English Grammar to EFL Learners - Hakami, Hamza Ali Othman; Abdelrahman, Abdallah Bani (Journal of Educational and Psychological Sciences, 2019)
This study aimed at exploring the effects of using games in teaching/learning English grammar on students' perceptions and attitudes.. The sample of the study was distributed on 50 Saudi male students majoring in English. The Data was collected from learners through a pre-test and a post-test conducted at the end of the grammar course. The results of the study indicated that students have a favorable perception towards games use in their grammar classroom. The study also revealed that students benefit from using games in increasing their interest and motivation to use English to interact with, and get feedback from classmates and teachers.
Keywords: English grammar; English as a foreign language; game; technology